7-Benzyl-2-[(cyclopropylmethyl)amino]-3-phenyl-5,6,7,8-tetrahydropyrido[4′,3′:4,5]thieno[2,3-d]pyrimidin-4(3H)-one - Hong Chen (Acta Crystallographica Section E, 2011)
There are two independent molecules in the asymmetric unit of the title compound, C26H26N4OS. In each molecule, the thienopyrimidine fused-ring system is essentially planar with a maximum deviation of 0.0409 (18) for the N atom. In one molecule, this ring system forms diherdral angles of 84.8 (1) and 67.6 (1)° with the adjacent phenyl and benzyl rings, respectively, while the corresponding angles in the other molecule are 77.9 (1) and 66.5 (1)°.